STATUS GIZI BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA LANJUT USIA DI DESA GIRISEKAR WILAYAH KERJA PUSKESMAS PANGGANG II KABUPATEN GUNUNGKIDUL - Siti Uswatun Chasanah; Patria Asda (Universitas Veteran Bangun Nusantara, 2022)
Background: The increasing number of elderly population has an impact on the pattern of degenerative diseases, metabolic diseases and psychosocial disorders. One of the factors that trigger hypertension is an unbalanced nutritional status. Excess nutrition is associated with prosperity and lifestyle. The occurrence of hypertension is influenced by unhealthy diet, smoking habits, alcohol consumption, stress and lack of physical activity. Research objectives: To know the relationship between nutritional status and the incidence of hypertension in the elderly in Girisekar Village, the working area of Panggang II Public Health Center, Gunungkidul Regency.Research method: Analytical survey research with cross sectional study design. The population in this study were elderly> 60 years who were active in the elderly posyandu. Sampling with simple random sampling, the number of samples is 191 people. Data collection tools for questionnaires and measurement of BMI and blood pressure. Data analysis using the Spearmen Rank test.Results: The results showed that the nutritional status of underweight had level 1 hypertension with 23 people (23.9%), normal nutritional status had level 1 hypertension with 35 people (36.5%) and fat nutritional status had level 1 hypertension. 38 people (39.6%). The Spearmen Rank test shows that the value of p = 0.001, which means there is a relationship between nutritional status and the incidence of hypertension in the elderly in Girisekar Village, the working area of Panggang II Public Health Center, Gunungkidul Regency.Conclusion: The higher the nutritional status or fat, the higher the risk of experiencing hypertension in the elderly in Girisekar Village, the working area of Panggang II Health Center, Gunungkidul Regency.